2016
DOI: 10.1111/jzo.12342
|View full text |Cite
|
Sign up to set email alerts
|

Virtual plaster cast: digital 3D modelling of lion paws and tracks using close‐range photogrammetry

Abstract: The ecological monitoring of threatened species is vital for their survival as it provides the baselines for conservation, research and management strategies. Wildlife studies using tracks are controversial mainly due to unreliable recording techniques limited to two-dimensions (2D). We assess close-range photogrammetry as a low-cost, rapid, practical and reliable field technique for the digital threedimensional (3D) modelling of lion (Panthera leo) paws and tracks. Firstly, we tested three reconstruction para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…This also probably contributed to prediction error. So, further studies may find it necessary to develop software technology to automatically extract the body measurements of Amur tigers, or to develop new methodology to eliminate parallax error, such as 3D geometric morphometrics (Marchal et al 2016(Marchal et al , 2017.…”
Section: Discussionmentioning
confidence: 99%
“…This also probably contributed to prediction error. So, further studies may find it necessary to develop software technology to automatically extract the body measurements of Amur tigers, or to develop new methodology to eliminate parallax error, such as 3D geometric morphometrics (Marchal et al 2016(Marchal et al , 2017.…”
Section: Discussionmentioning
confidence: 99%
“…Digital photogrammetry techniques such as "Structure from Motion", able to calculate the relative three-dimensional positions of points on an object by monitoring their motion across a number of overlapping images from a single moving camera [14], are increasingly used within academia to process survey images into three-dimensional spatial data such as textured polygonal models. Numerous studies have shown its effectiveness in the reconstruction of topology [15][16][17][18][19], archaeological sites [20], animal morphology and tracks for ecological monitoring [21]. The procedure follows three main steps: (1) matching feature points are mapped across multiple overlapping images to form tie points.…”
Section: Nest Reconstructionmentioning
confidence: 99%
“…Photogrammetry was employed by Faulkner [ 58 ], who studied the usability of applying the commercially available software package PhotoScan [ 59 ] to reconstruct 3D shoe impressions. Photogrammetry is used to construct a 3D model based on typically two or more 2D images, taken from different angles (typically the more images are used, the better the resulting 3D model is [ 60 ]). To this end, 3D data was reconstructed from impressions in sand from a used running shoe.…”
Section: Shoemarksmentioning
confidence: 99%